Lobsters : (Blackwell Pub, 2006)
Lobsters are one of the most commercially important groups of animals harvested and farmed throughout the world. Bringing high prices on the market and the table, the results and yields of farmed species has seen continued growth. Under the Editorship of Bruce Phillips an international team of authors provide exhaustive coverage of these fascinating creatures, stretching from growth and development to management and conservation, providing the reader with: Key information for lobster farmers and harvesters. Organisation of the species by genera for ease of use. Coverage of parasites, pathogens and commensals; their impact, detection and measurement. Fisheries scientists, aquaculture personnel, aquatic and invertebrate biologists, physiologists, ecologists, marine biologists and environmental biologists will all find this a vital source of reference. Libraries in universities and research establishments where biological and life sciences and fisheries and aquaculture are studied and taught will find it a valuable addition to their shelves.